ىيئات المشاركة والطعن في الوظيفة العامة 199/ حسب المرسوم - عباس, فوزي; بن عروس, بشرى (University of Eloued جامعة الوادي, 2021)
المرسو جاء في الوقت المناسب ولو أنو تأخر قميلا ليكرس مساعي الدولة الج ا زئرية الجديدة لتكريس مقومات النجاح والبناء العصري والحضاري لبموغ الغد المشرؽ فييئات المشاركة والطعف في قطاع الوظيفة العامة كي تمعب دو ا ر ىاما في رفع الغبف عف الموظؼ 199 ( كثمرة مف ثمار إصلاح الوظيفة العامة واعطاء / العمومي فجاء المرسو التنفيذي ) 20 الآليات القانونية والحقوقية لمموظؼ ولممثمي الموظفيف في ىيئات المشاركة والطعف في الدفاع عف الموظؼ إذا توفر لي الفضاء والظروؼ المناسبة مف ديمق ا رطية حقيقية وعدؿ سائد وعدالة نزيية وقانوف مكرس وسائد عف الجميع وحرية وشفافية ون ا زىة لتؤدي ىيئات المشاركة والطعف وظيفتيا المرجوة منيا. ويعود الأمؿ الذي يأممو الموظؼ في تحسيف حقوقو وصورة المؤسسات العمومية لبموغ الجودة في الأداء الوظيفي و الحكامة و الحوكمة في التسيير الإداري لتتغمب عمى سوء التسيير في الإدارة الج ا زئرية والقضاء عمى البيروق ا رطية والفساد الإداري لإعادة ضبط مؤشر الاصلاح عمى الصورة الجميمة لمج ا زئر الجديدة التي يتمناىا أبنائيا والتي حم بيا الشيداء البررة والمجاىديف المخمصيف بمؤسسات وىيئات المشاركة والطعف مبنية عمى حسف التمثيؿ والعمؿ التشاركي والتشاور لتحسيف الخدمة العمومية وضماف حياة كريمة لمموظفيف وعدالة اجتماعية وتطوير لدورىا الرقابي وأعطى الضمانات الكافية لمموظؼ لرفع الغبف والظم عميو مف تعسؼ الإدارة إذ لعبت ىيئات المشاركة والطعف دورىا المنوط بيا والمأموؿ منيا لتعزيز قي التعاوف ا ولمساىمة والعمؿ التشاركي وتحمؿ المسؤولية بأمانة واخلاص وتفعيؿ لسيادة القانوف وتعزيز قي العدؿ والعدالة لتجني ثمار المرسو التنفيذي بتفعيؿ ىيئات المشاركة والطعف في الوظيفة العامة.The decree came at the right time, even if it was a little late, to devote the efforts of the new Algerian state to devote the elements of success and modern and civilized construction to reach a bright tomorrow. The fruits of reforming the public office and giving legal and juridical mechanisms to the employee and employee representatives in the participation bodies and challenging the employee’s defense if they have the space and appropriate conditions of real democracy, prevailing justice, impartial justice and a dedicated and prevailing law for all, freedom, transparency and integrity for the participation and appeal bodies to perform their desired function. The hope that the employee hopes will improve his rights and the image of public institutions, to achieve quality in job performance, governance and governance in administrative management, to overcome mismanagement in the Algerian administration and to eliminate bureaucracy and administrative corruption, to reset the reform index on the beautiful image of the new Algeria that its sons wished and dreamed of by the righteous martyrs. The loyal mujahideen in the institutions and bodies of participation and appeal are based on good representation, participatory work and consultation to improve the public service and ensure a decent life for employees, social justice and the development of its oversight role. And participatory work and bearing responsibility honestly and faithfully and activating the rule of law and promoting the values of justice and justice to reap the fruits of the executive decree by activating the participation bodies and challenging the public job.
مذكرة ماستر